Development of Animation Video Media in Science Subjects for Class VIII SMP - Putri, Juliana Eka; Syafril, Syafril; Kurnia Yusri, Meldi Ade; Masnur, Alkadri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The development of Animation Videos in the Science Subject for 8th Grade at SMPN 20 Padang is motivated by the fact that teachers have not yet used appropriate learning media in the teaching process, students are passive and less participative in the learning process, resulting in low learning outcomes. This research aims to produce valid and practical animated video products that can be used in the learning process. The type of research used is research and development or Research and Development (R&D). The development model used in this study is the 4D model. The 4D model consists of 4 stages: define, design, develop, and disseminate. The product validity test was validated by three validators, consisting of one content validator, namely the science subject teacher for Class VIII at SMPN 20 Padang, and two media validators, namely lecturers from the Department of Curriculum and Educational Technology at Universitas Negeri Padang. The practicality test of the product was conducted with students of class VIII.4 at SMPN 20 Padang. The results of the development of this animation video were obtained through validity and practicality tests. The validity test by subject matter experts yielded an average score of 4.6 with the category